1977
DOI: 10.1149/1.2133657
|View full text |Cite
|
Sign up to set email alerts
|

Double Layer Capacitance and Charging Rate of Ultramicroporous Carbon Electrodes

Abstract: Adsorption of ions from aqueous solutions into pores, as narrow as 3.7Å was observed, using linear sweep cyclic voltametry. The conductivity of the solution in pores of less than 7Å diameter is several orders of magnitude lower than that of a free 0.1N normalNaCl solution in contact with the carbon electrode. It seems negligibly slow in pores of less than 3.7Å diameter, which are still completely filled with water. Highly oxidized ultramicroporous carbons show much lower double layer capacitance at positive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
0
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(70 citation statements)
references
References 12 publications
2
65
0
3
Order By: Relevance
“…Several experimental and theoretical studies suggested that ionic conductivity in pores is lower than bulk ion conductivity because of electrostatic interaction between ions and pore surface. 24,25 In this particular system, it is very possible that the pore surface is negatively charged upon a negative polarization and has a stronger attraction for the quaternary ammonium ions. This would explain why the ionic conductivity and rate capability is lower at 1.0 V than at 3.0 V ͑vs.…”
Section: Resultsmentioning
confidence: 99%
“…Several experimental and theoretical studies suggested that ionic conductivity in pores is lower than bulk ion conductivity because of electrostatic interaction between ions and pore surface. 24,25 In this particular system, it is very possible that the pore surface is negatively charged upon a negative polarization and has a stronger attraction for the quaternary ammonium ions. This would explain why the ionic conductivity and rate capability is lower at 1.0 V than at 3.0 V ͑vs.…”
Section: Resultsmentioning
confidence: 99%
“…The amount of CO-evolving groups does not change substantially, whereas the groups responsible for the CO 2 evolution significantly increased (from 0.2 to 0.8 mmol/g). When moderate oxidation takes place, the morphology of the carbon material does not change significantly, although some oxygen functional groups can be created at the surface of the material (i.e., hydroxyl groups) that could lead to an improvement in wettability [32] and/or could lead to enhanced specific capacitance values [33]. However, a strong oxidation can lead to deeper structural modifications that can cause the degradation of the carbon material (i.e.…”
Section: -Results and Discussionmentioning
confidence: 99%
“…[7] Die architektonische Verbesserung der Elektrodenoberflä-chen hin zu einem besseren Nutzungsgrad hätte weitreichende Folgen für Energiespeicherungs-und Umwandlungstechnologien wie Kondensatoren, Batterien, Brennstoffzellen und Elektrolysatoren.…”
Section: Einführungunclassified